2017
DOI: 10.1016/j.gie.2016.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel tablet application for improvement in colonoscopy training and mentoring (with video)

Abstract: Background and Aims: Endoscopic training can be challenging for the trainee and preceptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…In a randomized-control trial of eight telemedicine and eHealth students, Budrionis et al (2016) reported that those who supplemented their training and mentoring with telestration completed tasks 33% faster, as well as having fewer miscommunications than those who did not utilize telestration. This reaffirms the view that a combination of telestration and verbal feedback can mitigate misinterpretations and, when paired with interactive elements, results in a higher standard of education (Laborde et al, 2017). Bogen et al (2013) support this viewpoint, inferring that utilizing telestration enhances procedural and medical knowledge transfer; Feng et al (2017) cite a correlation between knowledge gained and reduced effort to acquire that knowledge.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…In a randomized-control trial of eight telemedicine and eHealth students, Budrionis et al (2016) reported that those who supplemented their training and mentoring with telestration completed tasks 33% faster, as well as having fewer miscommunications than those who did not utilize telestration. This reaffirms the view that a combination of telestration and verbal feedback can mitigate misinterpretations and, when paired with interactive elements, results in a higher standard of education (Laborde et al, 2017). Bogen et al (2013) support this viewpoint, inferring that utilizing telestration enhances procedural and medical knowledge transfer; Feng et al (2017) cite a correlation between knowledge gained and reduced effort to acquire that knowledge.…”
Section: Introductionsupporting
confidence: 52%
“…As evidenced by Table 2, video telestration appears to mitigate inherent differences of recallability between players, with those who experienced telestration exhibiting less variation of recall than those who did not experience telestration. Similarly, in bridging gaps in expert knowledge between coaches and players, video telestration appears to have the same effect in bridging gaps in cognitive capabilities between players, eliciting improvements in learning quality (Laborde et al, 2017). Overcoming inherent differences in cognitive function is also mirrored in the barriers posed by differences in languages within playing squads.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Telestration (digital broadcast for remote viewing and interaction) is an established principle in both laparoscopic surgical and endoscopic fields,8–10 but it usually employed for training, supervision or mentorship, rather than facilitating interhospital referrals. The technology lends itself readily to such a use case, but platforms designed for general use (or use-non-specific scenarios) may be a hindrance to easy implementation.…”
Section: Introductionmentioning
confidence: 99%
“…While no prior studies have directly evaluated the impact of distraction on endoscopic training in a gastroenterology unit, some have shown detrimental effects on teamwork, workload, and stress on members of operating room teams [10]. Conversely, one prior study used a novel tablet application to focus mentor attention on trainee polyp detection, which resulted in reduced stress, quicker polyp identification, and improved educational satisfaction [11].…”
Section: Introductionmentioning
confidence: 99%